Genesis and Mineralogy of Teak-Supporting Soils in Seoni District of Madhya Pradesh - Pushpajeet L. Choudhari (Journal of the Indian Society of Soil Science, 2022)
Five typical pedons having their parental legacy with basalt and occurring on different landforms were studied in forest area of Seoni district, Madhya Pradesh for understanding their mineral make-up and genesis. Semi-quantitative analysis of clay fractions indicated that soils clays are dominant in smectites followed by vermiculite (P1), kaolin (P3 and P5) and mica with traces of quartz and feldspar in all the pedons, barring pedon 4, which was dominated by kaolin. Inspite of the similar parent material and climatic condition, the formation of Alfisols, Entisols and Inceptisols might be attributed to the effect of climate, slope and/or drainage. The presence of kaolin and non-calcareous nature, indicated that these soils were formed initially under an earlier humid climate, while smectites, developed on depressions were retained up to the present climate due to non-leaching environment.